Forensic Assessment With the PAI in Correctional Samples: Implications for RNR: - Toop, Carissa (Criminal justice and behavior, 2019)
The present investigation examined Risk-Need-Responsivity (RNR) correlates of Personality Assessment Inventory (PAI) scores in a sample (N = 377) of offenders with diverse criminal histories. It was hypothesized that PAI scales with content reflective of criminogenic needs would be associated with recidivism while those indicative of major mental illness and behavioral disruption would be positively linked to responsivity variables. Several PAI scales predicted general and violent recidivism, particularly those reflective of criminogenic need. More serious profile patterns were associated with younger age, less education, lower cognitive ability, and sexual offense treatment attrition, per the responsivity principle. Finally, an exploratory factor analysis identified four PAI factors: Major Mental Illness, Extraversion, Paranoia, and Antisociality. Antisociality scores were the most predictive of general and violent recidivism. Antisociality and Major Mental Illness scores also predicted treatment attrition. Study findings suggest that the PAI can be a useful adjunct to standardized risk and need measures for RNR-informed assessment.